O-219 Donor conception and Commercial Genomics: how are donor conceived people, their parents and donors using direct-to-consumer genetic testing?. (30th June 2022) - Frith, L; Gilman, L; Redhead, C; Fox, M; Hudson, N; MacCallum, F; Kirkham Brown, J
Abstract: Study question: How do donor conceived people, their parents and donors use direct-to-consumer genetic testing (DTCGT)? Summary answer: DTCGT is changing how information about donor conception is accessed and managed by parents, donors and donor conceived people. What is known already: Following the development and rapid expansion of DTCGT, there have been claims that 'anonymity is dead' in relation to donor conception (Darroch & Smith, 2021; Harper et al., 2016). Small-scale studies (Crawshaw, 2018) and media articles have reported that donor conceived adults are often finding out about the circumstances of their conception after using DCTGT. However, there is a gap in the evidence about how donor conceived people already aware of their donor conception, as well as parents through donor conception and donors, are using DTCGT. Study design, size, duration: The ConnecteDNA project is an ongoing qualitative research study (March 2021-February 2024). It investigates how people in the UK, involved in donor conception, are impacted by DTCGT and considers the implications for policy and practice. This presentation focusses on phase two of the project: in-depth interviews with parents through donor conception, donors and donor conceived adults who have used, or considered using, DTCGT. Participants/materials, setting, methods: So far, six donors, 13 parents through donor conception and 18 donor conceived adults have been interviewed via telephone or video call. Interviews are ongoing until September 2022. Participants were recruited by advertising the project via a range of support groups and organisations for donor conception and/or DTCGT user communities. Main results and the role of chance: Our findings show that people involved in UK donor conception are using DCTGT to access and manage information about donor conception. This includes donor conceived people, previously unaware of the circumstances of their conception, discovering they are donor conceived after using DTCGT. We have found that donor conceived people, already aware that they are donor conceived, may also use DTCGT in search of information about 'donor relatives' and/or their genetic make-up, including understandings of their ethnicity and health risks. Furthermore, some donors are using DTCGT to make themselves contactable to people conceived via their donation(s), whilst others are traced via relatives who have used DTCGT. Parents through donor conception may use, or consider using DTCGT, to trace people related to their children through donor conception. This may be done when the child is very young, with the intention of finding relatives (particularly half siblings) who they can then grow up with. Others take a more responsive approach, only using DTCGT to support a child's request or interest in more information. DTCGT is also used to trace genetic relatives alongside, or instead of, 'official' routes for accessing information about donor conception, as well as social media and public records. Limitations, reasons for caution: Participants in this study are self-selecting and some groups may be under-represented in our sample (e.g. fathers through donor conception). We make no claims regarding the relative prevalence of different views and experiences. However, findings demonstrate the range of ways in which people involved in donor conception are using DTCGT. Wider implications of the findings: DTCGT is transforming how people involved in donor conception seek information about genetic relatives. UK law and HFEA policies will require reform to account for this. Professionals who work with people using, or considering, donor conception, should make their clients aware of the potential uses and outcomes of DTCGT. Trial registration number: Not applicable